A prospective cohort study to assess the risk factors of failed extubation in mechanically ventilated pediatric patients admitted to the intensive care unit. - M. A. Abdelnaser; H. M. Sakhr; A. Fetouh; A. A. Sabry; H.M. Qubaisy; A. M. Ismail (Pediatric Anesthesia and Critical Care Journal, 2022)
Introduction Failed extubation is a challenge in the intensive care unit. It can cause increased morbidity, and mortality in addition to higher costs due to prolonged hospital stay. We aimed to determine the risk factors of failed extubation and predictors of weaning success among mechanically ventilated children. Material and Methods It was a prospective cohort study for children on mechan- ical ventilation for longer than 24 hrs where they were followed up for 48 hrs after extubation. Failed extubation is the need for tube reinsertion within 48 hrs post-extuba- tion. Demographic characteristics and mechanical venti- lation parameters were evaluated. Arterial blood gas val- ues and rapid shallow breathing index (RSBI) were as- sessed on admission, before weaning from mechanical ventilation, and during weaning. Results Failed extubation was seen in 17.5% of pa- tients;53.9% of them were ≤one year and 26.9% were between one and five years while 19.2% were Anaesthesia and ICU, Faculty of Medicine, Assiut Univer- Keypoints Failed extubation is more common in young children, in patients with respiratory illness, and those receiving prolonged mechanical ventilation. ≥5 years. Of patients with a failed extubation, respir- atory illnesses were the principal cause of ventilation (50%) followed by cardiac surgery ventilated cases (23% each), neurological (15.4%), envenomation (7.7%), and lastly drug intoxication cases (3.8%). Duration of ventilation, PaCO2, and RSBI were sig- nificantly higher in cases with failed extubation than others. Body Weight, Glasgow Coma Scale, tidal volume, PaO2, and PaO2/FiO2 were significantly higher with extubation success. PaCO2 < 45 showed the highest sensitivity followed by RSBI, breaths/min/ml/kg <7 for extubation success. Conclusion Based on the result of this study, failed extubation is more common in young children, in patients with respiratory illness, and those receiving prolonged mechanical ventilation. Close monitoring of oxygen- ation indices, and PaCO2 can avoid hazardous prem- ature extubation. PaCO2 < 45 and rapid shallow breathing index with a threshold of <7 breath/min/ml/kg are good predictors for extubation success and dependable parameters for extubation timing in children.